Health literacy for patient safety in the neonatal ICU with the nursing team: scoping review protocol (Research, Society and Development, 2022)
Objective: To map the evidence about health literacy strategies focused on patient safety with the nursing team in a Neonatal Intensive Care Unit. Methodology: This is a Scoping Review. Review question: What are the health literacy strategies focused on patient safety with the nursing team in a neonatal intensive care unit? Inclusion and Exclusion Criteria: Studies referring to population, concept and context will be considered. There will be no time cut. In English, Spanish and Portuguese. Abstracts and posters published in scientific events, as well as opinion articles, were excluded. Search strategy: The search strategy will consist of three steps/search. Selection of studies: The PRISMA flowchart will be used. Data extraction: An instrument will be used whose objective will be to answer the guiding question of this review. Data synthesis: Still under construction. The results will be described and presented in tables and graphs. Presentation and interpretation of results: Still under construction The results of this study will be presented at events, and through the translation of knowledge.